Features of the water regime and photosynthesis in hybrid forms of cherry plum under the dry wind season conditions - A. V. Grigoriev; R. A. Pilkevich; L. A. Lukicheva; T. B. Gubanova; V. M. Gorina (Труды по прикладной ботанике, генетике и селекции)
Background. The results of a study on the drought resistance of cherry plum hybrid forms are presented. Water retention capacity of leaves and chlorophyll fluorescence were measured under the simulated conditions close to the dry wind season.Materials and methods. The water regime parameters were studied for five cherry plum genotypes in 2021 and 2022. Leaves of four hybrid forms developed at the Nikita Botanical Gardens and the reference cherry plum hybrid cultivar ‘Rumyanaya Zorka’ (Prunus rossica Erem.) were taken into the experiments. Using the guidelines by G. N. Eremeev and A. I. Lishchuk, a series of experiments on controlled leaf wilt at the air temperature of +27°C and relative humidity of 30% were conducted on cherry plum to assess the functional state of the photosynthetic apparatus during the development of water stress under dry wind conditions. The experiments were carried out in a Binder climate chamber. Chlorophyll fluorescence was measured using a portable Floratest fluorometer. The measurements were based on the parameters of the chlorophyll fluorescence induction curve (CFI) obtained on native leaves. The leaves of cv. ‘Rumyanaya Zorka’ in the state of complete watering served as the reference.Results and discussion. Dependence was identified between chlorophyll fluorescence and moisture content in the leaves of the studied samples. The hybrids were found to respond to drought in different ways. A relatively increased ability to retain moisture during dehydration was observed in form 12/26 whose leaves gave off moisture more slowly and restored their turgor better. It is promising for cultivation in areas with insufficient water supply. Form 99/36 had the lowest potential drought resistance. Forms 99/14 and 9/28 occupied an intermediate position.